EPIDEMIOLOGY OF CHAGASIC CARDIOMYOPATHY IN HONDURAS - Sierra, Manuel; Maguire, James; Echeverz, Carlos; Wypij, David; Ponce, Carlos; Cosenza, Humberto; Padget, Dennis; Bogran, Marco; Ponce, Elisa de (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
EPIDEMIOLOGY OF CHAGASIC CARDIOMYOPATHY IN HONDURAS